PSYCHOLOGICAL WELL-BEING OF PREGNANT UNMARRIED WOMEN: A CASE STUDY - Feti Astuti (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
At the beginning of the incident, women who experience pregnancy outside of marriage have poor self-acceptance. This is due to the negative stigma from the surrounding environment and the response of parental disappointment, especially if the partner does not want to take responsibility. This research is qualitative research using a case study approach. The results showed that participants eventually had good self-acceptance. This is because participants get support from their family and close friends. The religiosity factor was also found in participants, which helped them have hope.